Preparing teachers at the University of Virginia’s college at wise - Jeffrey Cantrell, R.; Askins, G. Jewell (Revista Fuentes, 2011)
The purpose of this article is to describe how teacher education candidates at The University of Virginia’s College at Wise (UVa-Wise) in the United States are trained and become eligible for professional teaching licenses in grades 6-12 in the Commonwealth of Virginia. First, the authors offer a brief overview of the College and the collaborative efforts between the UVa-Wise Department of Education and other academic disciplines. The authors identify specific program endorsement areas and grade levels in which UVa-Wise TEP candidates are awarded their degree. They summarize their respective curricula in endorsement areas that candidates are required to complete to become eligible for their professional licenses in their respective teaching endorsement areas. Topics of discussion include: 1.) Requirements that candidates must meet for admission into the UVa-Wise teacher education program; 2.) Professionals’ expectations regarding their admission and continuation in the UVa-Wise teacher education program; and 3.) Admission requirements to the student teaching internship required to complete the program. Additionally, they discuss the roles of the Virginia Department of Education and the Virginia Board of Education in the teaching endorsement approval process for all teacher education programs in Virginia. Finally, the process of how teacher education programs can become recognized by a national accrediting organization (more specifically, the Council for Accreditation of Teacher Education) is briefly examined. El objetivo de este artículo es describir la formación de los estudiantes de Formación del Profesorado en la Universidad de Virginia de Estados Unidos y cómo llegan a ser docentes para la Enseñanza Primaria (Grados 6-12) en el Estado de Virginia. Los autores presentan, en primer lugar, una breve visión general del College y los esfuerzos colaborativos entre el Departamento de Educación de UVA-Wise y otras disciplinas académicas. Los autores identifican las áreas específicas de apoyo a los programas y las etapas y grados de los candidatos a la Formación del Profesorado en UVA-Wise para licenciarse. Asimismo, se resumen los respectivos planes de estudio que deben completar los estudiantes para adquirir la licencia profesional en sus correspondientes áreas. Los temas de la presente exposición incluyen: 1. Requisitos que los candidatos necesitan para ser admitidos en el programa de Formación del Profesorado en UVA-Wise; 2. Las expectativas de los profesionales en cuanto a su admisión y continuación en el mencionado programa; y 3. Los requisitos de admisión al periodo de prácticas, el cual es requerido para completar el programa. Se expone además, el papel que tiene el Departamento de Educación de Virginia y el Consejo de Educación para la aprobación de los programas dirigidos a la Formación de Profesores en Virginia. Finalmente, ha sido brevemente examinado, el reconocimiento otorgado a los programas de formación de profesores por parte de una organización nacional de acreditación (en concreto, el Consejo de Acreditación de Educación de Profesores).